Promotion of physical activity-related health competence using digital workplace-based health promotion: a pilot study for office workers - Oppermann, Leonard; Dierks, Marie-Luise (Frontiers in Public Health, 2025)
IntroductionEngaging in health-enhancing physical activity (HEPA) can reduce the risk of developing chronic diseases, which is particularly important for office workers with sedentary lifestyles. Therefore, time- and location-independent interventions for increasing HEPA are necessary.MethodsTo achieve long-term changes in HEPA, interventions can be based on physical activity-related health competence (PAHCO). 48 office workers (83% female, 50 ± 8 years) completed an intervention consisting of bi-weekly exercise videos for 5 weeks, supplemented by PAHCO and anatomical education. The participants’ HEPA levels were measured using the Physical Activity, Exercise, and Sport Questionnaire (Bewegungs- und Sportaktivität Fragebogen; BSA-F)and a physical activity diary, with follow-up measurements at 3 months.ResultsThere was a significant increase in PAHCO (p = 0.002), especially in control competence (p < 0.001), after the intervention and at follow-up. The other sub-competences also increased, but not significantly. HEPA decreased after the intervention and at follow-up, but the decrease was not statistically significant.DiscussionPAHCO increases after the end of the intervention, especially through the sub-competence of control competence. The other two sub-competences also improved, but not significantly. Participating in the study had no impact on HEPA as an outcome of the PAHCO model. Our study provides preliminary evidence that PAHCO can be enhanced through digital, time- and location-independent interventions. Future research should utilize a randomized controlled design to be able to causally attribute the effects of PA interventions in office workers to the intervention and objective measurements for HEPA should be employed.